Compositional Strategies in Popular Song Form of the Early Twentieth Century - John Graziano (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
Popular song at the beginning of the twentieth century exhibited several new tendencies that, over time, became audience favorites. A new type of rude song, with syncopated melodies and vernacular lyrics (called by the unsavory term “coon song”), took audiences by storm. The general form used in the earlier songs—verse/chorus—still provided the basic structure. But the harmonies and internal structure of both sections moved in a new direction. As the popular music of Tin Pan Alley developed, song composers looked for new ways to vary the basic harmonic progressions in phrases that usually spanned eight measures. Among the variety of new forms was one—AABA—that would prove important to the future of popular song. In this paper, I explore the expansion of harmonic possibilities that took place in the chorus with the adoption of the AABA form during the late 1910s and ’20s. I have chosen songs from Broadway shows and film musicals (by Berlin, Burke, Gershwin, Henderson, Rodgers, Waller, and Warren) that demonstrate how composers began to move away from the basic dominant and subdominant alternations to explore increasingly complex strategies in the harmonic progressions that comprise the release (i.e., bridge) sections of the chorus. These explorations proved fruitful to the development of the form and provided a foundation for the introduction of chromatic progressions that evolved in the 1930s. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).